PENGARUH KEPERCAYAAN KEPADA PEMERINTAH NORMA SUBJEKTIF KUALITAS TERHADAP KEPATUHAN WAJIB PAJAK - Rimawati Qadariah; Nur Diana; Junaidi Junaidi (Universitas Islam Malang, 2021)
This study aims to determine the effect of the application of Trust to the Government, Subjective Norms, and Quality of Service on taxpayer compliance at KPP Pratama South Malang. This research is a quantitative research using primary data. The population in this study was 133,000 individual taxpayers registered at KPP Pratama South Malang. The size of the sample in this study was determined using the slovin method which resulted in 100 respondents. The sampling method used in this research is random sampling. Data collection in this study was carried out by distributing questionnaires to individual taxpayers at KPP Pratama South Malang. The analytical technique used in this research is multiple linear regression with the help of SPSS program. Based on the partial test results, it can be seen that Trust in Government and Service Quality have a positive and significant effect on individual taxpayer compliance. While the Subjective Norm has no effect on individual taxpayer compliance. Keywords: Trust in Government, Subjective Norms, Service Quality, Tax Compliance